Comparative assessment of macrophage responses and antileishmanial efficacy in dynamic vs. Static culture systems utilizing chitosan-based formulations - Alaa Riezk; Alec O’Keeffe; Katrien Van Bocxlaer; Vanessa Yardley; Simon L. Croft (PLoS ONE, 2025)
The discovery of novel anti-leishmanial compounds is essential due to the limitations of current treatments and the lack of new drugs in development. In this study, we employed the Quasi Vivo 900 medium perfusion system (QV900, Kirkstall Ltd, UK) to simulate physiological fluid flow, allowing us to compare macrophage responses and therapeutic outcomes under dynamic versus static conditions. After 24 hours, phagocytosis and macropinocytosis decreased in all cell types under flow conditions compared to static cultures. Under slow (1.45 x 10-9 m/s) and faster (1.23 x 10-7 m/s) flow conditions ((simulating in vivo lymphatic flow), phagocytosis decreased by around 42.55% and 56.98% in peritoneal macrophages (PEMs), 42.21% and 56.11% in bone marrow-derived macrophages (BMMs), and 49.75% and 63.32% in THP-1 cells, respectively. Similarly, macropinocytosis decreased by approximately 40.7% and 62.2% in PEMs, 34.8% and 60.9% in BMMs, and 33.3% and 59.3% in THP-1 cell line under this same conditions. In this study, we further assessed the impact of medium perfusion on drug efficacy and macrophage functions using a Leishmania major amastigote-macrophage assay. We evaluated the performance of both standard and nanoparticle-based drug formulations within dynamic and static culture systems. After 72 hours of medium perfusion, chitosan solution, blank chitosan-sodium tripolyphosphate (TPP) nanoparticles, and amphotericin B (AmB)-loaded chitosan-TPP nanoparticles exhibited a statistically significant reduction in antileishmanial activity by approximately 30-50% under slow flow conditions and 60-80% under faster flow conditions. In comparison, pure AmB showed a 40% decrease in efficacy at slow flow and a 67% decrease at faster flow, both statistically significant. These results highlighted the importance of considering fluid flow dynamics in in vitro studies for a more accurate simulation of in vivo conditions, potentially leading to better therapeutic strategies for cutaneous leishmaniasis (CL).